Doctrine of Force Majeure in Civil Law Due to Customs Regulatory Intervention in Indonesian Bonded Zones - Erwin Erwin (Law Development Journal, 2026)
This article aims to reconstruct the force majeure doctrine in Indonesian civil law to accommodate state regulatory intervention in customs within bonded zones. The classical force majeure doctrine under Articles 1244–1245 of the Indonesian Civil Code traditionally focuses on natural disasters and unforeseeable events, leaving regulatory interventions unaddressed. The urgency lies in increasing state regulatory changes in customs policies mandatory e-seals, transportation restrictions, expanded quarantine inspection, surveyor report obligations, and proposed reduction of domestic sales caps that disrupt contractual performance in export-oriented industries within bonded zones. The novelty is the "regulatory force majeure" concept, recognizing legitimate state regulatory interventions as a standalone ground for force majeure, integrating public and private law perspectives. The research method is normative legal research using statute, conceptual, and case approaches, with primary legal materials including the Indonesian Civil Code and Customs Law, and secondary materials consisting of accredited national journals (SINTA) and international literature. The results demonstrate that the classical force majeure doctrine fails to accommodate regulatory interventions due to the absence of explicit recognition, lack of objective parameters (externality, unforeseeability, irresistibility, causation), and absence of integration between administrative and contract law. This article concludes that the regulatory force majeure concept offers a doctrinal reconstruction providing legal certainty in resolving contractual disputes arising from state regulatory interventions in bonded zones.